2021
DOI: 10.1111/ijd.15512
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of zinc oxide nanoparticle‐coated socks compared to uncoated socks for the prevention of pitted keratolysis: a double‐blinded, randomized, controlled trial study

Abstract: Background Pitted keratolysis (PK) and bromodosis have negative impacts on the quality of life especially for military personnel. The antibacterial efficacy and safety of zinc oxide nanoparticles (ZnO-NPs) make them a suitable additive for textiles. We aim to establish the ability of ZnO-NP-coated socks to prevent PK and bromodosis in a real-life setting.Materials and methods A double-blinded, randomized, controlled trial was conducted in January 2019. Naval cadets assigned to a 14-day field training course we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…21 Previous research has shown that ZnO-NP-coated socks can prevent PK among naval rating cadets after a 14-day training course. 16 However, the effectiveness of ZnO-NP-coated socks as a treatment for PK has not previously been reported. Our study is the first to demonstrate the ability of these socks to treat PK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…21 Previous research has shown that ZnO-NP-coated socks can prevent PK among naval rating cadets after a 14-day training course. 16 However, the effectiveness of ZnO-NP-coated socks as a treatment for PK has not previously been reported. Our study is the first to demonstrate the ability of these socks to treat PK.…”
Section: Discussionmentioning
confidence: 99%
“…ZnO nanoparticles are known for their antibacterial properties, which mainly target the cytoplasmic membrane of bacteria 21 . Previous research has shown that ZnO‐NP‐coated socks can prevent PK among naval rating cadets after a 14‐day training course 16 . However, the effectiveness of ZnO‐NP‐coated socks as a treatment for PK has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations